Prevalence of cardiovascular risk factors in Lithuanian middle-aged subjects participating in the primary prevention program, analysis of the period 2009-2012 - Laucevi ius, Aleksandras; Rink nien, Egidija; Skujait, Agn; Petrulionien, aneta; Puronait, Roma; D enkevi i t, Vilma; Kasiulevi ius, Vytautas; Jatu is, Dalius; Ryliškyt, Ligita; Šlapikas, Rimvydas (Blood pressure, 2015)
Abstract Background. The aim of this study was to assess the prevalence and changes of cardiovascular risk factors in the middle-aged Lithuanian subjects after conducting the primary prevention program. Design and methods. Four cross-sectional investigations of cardiovascular risk factors were conducted in 2009 (n = 9625), 2010 (n = 7716), 2011 (n = 5018) and 2012 (n = 4348). The program recruited men aged 40-54 and women aged 50-64 without overt cardiovascular disease. Results. During the period 2009-2012, the mean number of risk factors significantly increased (from 3.95 to 4.03, p < 0.001), while the numbers of people having metabolic syndrome (from 34.1% to 28.7%; p < 0.001), arterial hypertension (from 60.2% to 54.5%; p < 0.001), the average body mass index (BMI) value (from 29.17 to 28.92 kg/m2; p = 0.001) and abdominal obesity (from 48.4% to 45.3%; p < 0.001) significantly decreased. The percentage of subjects with dyslipidemia, as well as the average values of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides, remained unchanged. The percentage of smoking subjects have significantly increased (from 19.3% to 22.7%; p < 0.001). Conclusions. The analysis showed that the prevalence of arterial hypertension, metabolic syndrome and obesity in Lithuania is slowly decreasing while conducting the primary prevention program; however, dyslipidemia, diabetes mellitus and smoking are still hard to manage for both genders.